Intensity‐modulated temperature sensor based on fiber interferometer with optical bandpass filtering. Issue 6 (June 2016) - Azmi, A. I.; Abdullah, A. S.; Mohd Noor, M. Y.; Mohd Supa'at, A. S.; Kassim, N. M.; Ngajikin, N. H.
ABSTRACT: An intensity‐modulated temperature sensor based on fiber Mach‐Zehnder interferometer (MZI) is proposed and demonstrated. The sensor is constructed using single mode fiber (SMF) and multimode fiber (MMF) in SMF‐MMF‐SMF‐MMF‐SMF sequence. The sensing system is power‐interrogated, relies on an optical bandpass filtering of the sensor output at a predetermined wavelength which converts any change in sensor spectra into power change. This sensing scheme is very cost effective, as the temperature can be directly quantified from photodetector voltage measured at the filter output. Furthermore, sensor fabrication only involves conventional fusion splicing process between standard SMF and MMF. Experimental result shows that a sensor with length 20 mm produces linear response of −0.48 mV/°C at 1532 nm passband wavelength, good long‐term stability with negligible voltage drift and fluctuation, and wide measurement range within 30–180°C. The proposed scheme potentially can be applied in fiber interferometer sensors for measurement of other physical parameters such as strain, refractive index and vibration. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:1458–1462, 2016